Prevalence of Anemia and Morphological Variation in RBC among COPD Patients admitted at a Tertiary Health Care Center, Kathmandu, Nepal (Nepal Medical College Journal, 2021)
Many studies have depicted that anemia is one of the most common co-morbidity among Chronic Obstructive Pulmonary Disease (COPD) patients. Therefore, its correction in those patients is an important aspect of the treatment protocol. Our study was designed to explore the prevalence of anemia and morphological alteration, if any, in RBC among COPD patients. The study was conducted from November 2020 to June 2021 among the COPD patients admitted in the Medical ward of Nepal Medical College Teaching Hospital. If hemoglobin level was